Abrigos de mosquitos Culex (Culex) em zona rural (Diptera: Culicidae) Resting places of mosquitoes Culex (Culex) in rural zones (Diptera: Culicidae) - Almério de Castro Gomes; Oswaldo Paulo Forattini (Universidade de São Paulo, 1990)
As atividades antrópicas levadas a cabo em zona rural têm afetado o comportamento de mosquitos Culex (Culex), motivo pelo qual foi realizada investigação para observar seus abrigos naturais em área de pastagem, margem e interior de matas primitivas ou residuais. Foram escolhidas três localidades com características mesológicas diferenciadas pelo tipo de atividade humana, todas situadas na região do Vale do Ribeira, Estado de São Paulo, Brasil. As espécies mais abundantes foram Cx. mollis (28,0%), Cx. declarator (25,0%), Cx. lygrus (13,0%) e Cx. coronator (9,6%). O conjunto Cx. Bidens + Cx. dolosus + Cx. chidesteri, de hábito mais urbanizado, foi capturado em número muito reduzido. Com relação aos ambientes pesquisados, a mata contribuiu com 2.281 indivíduos (71,4%), sugerindo ser local de abrigo preferido pelo grupo, exceto para Cx. quinquefasciatus. Avaliou-se o potencial de domiciliação de cada espécie e suas conseqüências para a população humana. The human activities carried out in rural zones have been affeecting the behavior of mosquitoes of the Culex (Culex) subgenera, which was the reason for undertaking this investigation with a view to registering data on the natural resting places in pastures and on the edge of or within primitive and residual forest areas. Three localities with different mesological conditions, as to type of human activity, all them situated in the Ribeira Valley region of S. Paulo State, Brazil, were chosen. The species most abundantly found were Cx. mollis (28.0%), Cx. declarator (25.0%), Cx. lygrus (13.0%) and Cx. coronator (9.6%). The collection of mosquitoes Cx. bidens + Cx. dolosus + Cx. chidesteri, known to be more urban, was much smaller than that of any other species of the group. With reference to outdoor environments, woodland contributed with 2,281 individuals (71.4%) suggesting their preference for this resting place, except for Cx. quinquefasciatus. Results are evaluated for the determination of the potential domicilation of each species and consequence of the same for the human population.